2017
DOI: 10.1007/s00894-017-3274-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the crystalline environment on the third-order nonlinear optical properties of L-arginine phosphate monohydrate: a theoretical study

Abstract: A supermolecular approach combined with an iterative electrostatic scheme was employed to investigate the nonlinear optical properties of the hybrid L-arginine phosphate monohydrate crystal, the procedure being aided by DFT calculations. The supermolecular scheme basically treated the molecules surrounding the unit cell as point charges; this approximation results in rapid convergence, making it a feasible method. DFT functionals of different flavors were considered: B3LYP, B2PLYP, CAM-B3LYP, ωB97, and M06HF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Here we consider a single BRC molecule and through the CHELPG scheme the crystalline environment polarization is simulated by considering the atoms that surrounding the BRC molecule as point charges. The SM approach was used in several theoretical works ,, , and the obtained results were found close to the experimental ones. Particularly in ref , the DFT/CAM-B3LYP/6-311++G­(d,p) results for the nonlinear third-order susceptibility for a chalcone derivative have described satisfactorily the Z -scan experimental result of Prahbu et al…”
Section: Theoretical Calculations: Linear and Nonlinear Optical Prope...supporting
confidence: 62%
“…Here we consider a single BRC molecule and through the CHELPG scheme the crystalline environment polarization is simulated by considering the atoms that surrounding the BRC molecule as point charges. The SM approach was used in several theoretical works ,, , and the obtained results were found close to the experimental ones. Particularly in ref , the DFT/CAM-B3LYP/6-311++G­(d,p) results for the nonlinear third-order susceptibility for a chalcone derivative have described satisfactorily the Z -scan experimental result of Prahbu et al…”
Section: Theoretical Calculations: Linear and Nonlinear Optical Prope...supporting
confidence: 62%
“…The applicability of the SM approach is supported by its results close to the experimental ones [19][20][21]. Several recently published works use this technique due to the rapid convergence of NLO properties [22][23][24][25][26][27]. In the SM method, the atoms that form the surrounding molecules of the compounds are treated as point charges, since the interactions between molecules have a dominant electrostatic nature, taking into account long-range electrostatic effects [28,29].…”
Section: Methodsmentioning
confidence: 73%
“…The polarization of the crystalline environment was simulated by the supermolecule (SM) approach where the atoms of the molecules within the asymmetric unit are considered as point charges. This approach has been used in several works. , In ref , the authors showed that SM approach simulates the dipole moment with results close to the experimental values and in refs and , the authors simulate the macroscopic properties χ (1) and χ (2) of the crystal, with results close to those of experiments. Other techniques to calculate the macroscopic properties χ (1) and χ (2) can also be cited, e.g., the works by Seidler and Champagne. , However, although the SM has provided good results, it is worth mentioning that other factors can also affect the nonlinear properties of the crystal.…”
Section: Experimental and Computational Proceduresmentioning
confidence: 79%